Solution of Communication Services of Vehicle Mobile Terminals Based on LTE and Ev-Do Hybrid Networking - Fei Zhao; Wenjun Zhang; Yong Deng (Dianxin kexue)
The realization to communications services of intelligent vehicle mobile terminal was discussed.Technology solutions of network architecture，signaling procedure，network handover and QoS guarantee were proposed.And the specific technology implementation scheme was proposed.